Natural aspirin of some members of the Rosaceae and Salicaceae families - Yu. I. Korniievskyi; O. I. Panasenko; V. H. Korniievska; B. O. Varynskyi; M. M. Maletskyi (Zaporozhye State Medical University, 2022)
White willow Salix alba L., a member of the family Salicaceae is characterized by the presence of phenolic compounds and their glycosides (1.5-11.0 %), such as salicin, salicortin, salireposide, picein, triandrin, syringin, tremulacin, flavonoids (1-4 %) namely luteolin, apigenin, quercetin, quercimeritrin, cosmosin, diosmetin, tannins (8-20 %) i.e. catechins, anthocyanidins, halotanines of organic acids, ascorbic acid. Preparations of white willow bark are used as an antipyretic, anti-inflammatory, diaphoretic, analgesic, diuretic, and astringent. The rhizomes with roots of the commonly known dropwort or fern-leaf dropwort are Filipendula vulgaris Moench., member of the family Rosaceae are characterized by phenologicoside gaulterin, the hydrolysis of which produces salicylic aldehyde, tannins (up to 33 %), flavonoids, ascorbic acid, polysaccharides, starch. The herbs and flowers are used as anti-inflammatory, anti-rheumatic, vasodilator, gastric, and antiulcer agents. The aim of the work is to determine the composition of the white willow bark Salix alba L. tincture, a member of the willow family Salicaceae, using gas-liquid chromatography (GLC) and HPLC and to determine the composition of the tincture of the dropwort root Filipendula vulgaris Moench. family Rosaceae. Materials and methods. Raw materials (underground organs) of the dropwort Filipendula vulgaris Moench. and bark of the white willow Salix alba L., which were harvested in July 2020 at the ZSMU research site. Tinctures were prepared according to the production recipe (1:5) (extractant was 70 % ethanol), investigated by the gas chromatograph Agilent 7890B with mass spectrometric detector 5977B. The mass spectra library NIST 14 was used to identify the components. White willow bark tincture (70 % ethyl alcohol extractant) was used to determine the phenolic compounds content and salicylic acid derivatives. The study was performed by HPLC (high-performance liquid chromatography) and HPLC MS. Results. Qualitative and quantitative analysis of the components of Salix alba L. willow bark tincture was performed by gas-liquid chromatography, 39 components of different classes of biologically active compounds have been identified, among which the 10 components are predominated in quantitative content. The main one was Salicin (39.53 %). The GC analysis of the tincture of the dropwort roots, Filipendula vulgaris Moench., identified 34 components of different groups of biologically active compounds, dominated by 11 components, the main is Ethyl.alpha.-d-glucopyranoside (34.55 %). HPLC analysis confirmed the presence of phenolic compounds (flavonoids such as apigenin, and quercetin) and salicylic acid derivatives (glycoside salicin) in the tincture of white willow bark (Salix alba L.). Conclusions. By GC analysis the 39 components in tincture of white willow bark Salix alba L. were identified, 10 components were predominated, the main one was Salicin (39.53 %). The 34 components in the tincture of the dropwort roots, Filipendula vulgaris Moench., were identified, dominated by 11 components, the main was Ethyl.alpha.-d-glucopyranoside (34.55 %). The presence of phenolic compounds (flavonoids were apigenin and quercetin) and salicylic acid derivatives (glycoside salicin) was confirmed by HPLC MS in the tincture of white willow bark (Salix alba L.).